Grammaticalization of aindci, assim and logo as linking words: a study on the variety of the mato-grossense Portuguese - Lopes-Damasio, Lucia Regiane [UNESP]; Santos, Grasiela Veloso dos (Univ Federal Minas Gerais, Fac Letras, 2016)
This study approaches the items ainda (yet), assim (so) and logo (then), in corpus of letters written in the Captaincy of Mato Grosso by people who were connected to the local government and to the clergy, from mid -18th century to early 19th century. Based on presuppositions of Grammaticalization, quantitatively and qualitatively analyzed, it aims at finding a connection with results of other researches that belong to the same nature (LONGHINTHOMAZI, 2006, 2005, 2004; LOPES-DAMASIO, 2011a, 2011b, 2008), and which focused on the same items, in different linguistic varieties of the Brazilian Portuguese. About the study: (i) it confirmed the trajectory of changes of the items we focused on adverb > linking word > discourse marker (MD) with semantic changes that indicate certain gain of abstraction and pragmatic; (ii) it allowed us to find some expressive recurrence of ambiguous / non prototypical usages, associated with contexts that advantage the different forms of change in the relation between Source and Target; and (iii) it revealed these mato-grossense letters to be a linguistic-discursive environment that supports gradualness of linguistic changes that allows more grammatical items to emerge.
Keywords: grammaticalization; junction; adverbial basis